2018
DOI: 10.3390/nu10020238
|View full text |Cite
|
Sign up to set email alerts
|

Donor Human Milk Protects against Bronchopulmonary Dysplasia: A Systematic Review and Meta-Analysis

Abstract: Bronchopulmonary dysplasia (BPD) is the most common complication after preterm birth. Pasteurized donor human milk (DHM) has increasingly become the standard of care for very preterm infants over the use of preterm formula (PF) if the mother’s own milk (MOM) is unavailable. Studies have reported beneficial effects of DHM on BPD. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) and observational studies on the effects of DHM on BPD and other respiratory outcomes. Eightee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 62 publications
1
94
2
5
Order By: Relevance
“…Human milk feeding decreases the risk of NEC (28). Meta-analyses suggest a benefit in feeding mother's own milk (29) and pasteurized donor human milk (30) in the prevention of BPD. In organoids derived from the terminal ileum of mouse pups, human milk exosomes have been shown to attenuate LPS induced activation of TLR4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Human milk feeding decreases the risk of NEC (28). Meta-analyses suggest a benefit in feeding mother's own milk (29) and pasteurized donor human milk (30) in the prevention of BPD. In organoids derived from the terminal ileum of mouse pups, human milk exosomes have been shown to attenuate LPS induced activation of TLR4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, data suggesting a bene cial impact of maternal milk feeding on BPD were limited. Some investigators had concluded that maternal milk decreased incidence of BPD [7,[11][12][13][14], but others had not thought it useful [15]. Thus we can make two postulations: either high-volume maternal milk feeding daily directly impacts BPD or BPD has an obvious effect on volume maternal milk feeding .…”
Section: Discussionmentioning
confidence: 99%
“…(51) El inicio precoz de nutrición parenteral con aporte proteico de 3-4 g/kg/día, la estimulación trófica gastrointestinal y la alimentación exclusiva con leche de la propia madre o de donante también son factores preventivos. (68) La investigación de nutrientes que puedan ser de utilidad en la prevención o tratamiento de DBP, incluyen glutamina, cisteína y N-acetil cisteína, L-arginina y L-citrulina, ácidos grasos poli-insaturados de cadena larga ("PUFA"), inositol, selenio, y algunas vitaminas antioxidantes como la vitamina A. La evidencia muestra, que la vitamina A y los "PUFA" pueden prevenir DBP, y que la L-citrulina, puede convertirse en un nuevo método para tratar la hipertensión pulmonar (HP) crónica asociada con DBP.…”
Section: Hidratación Parenteral Y Nutriciónunclassified